Implementation of Didactical Design for Fraction Division Calculation Operation in Grade V Elementary School - Rosmayasari Rosmayasari; Didi Suryadi; Tatang Herman; Sufyani Prabawanto (International Journal of Artificial Intelligence Research, 2022)
This research is motivated by the existence of learning obstacles experienced by students in learning fraction division calculation material. The learning obstacle is caused by the learning design that is designed has not facilitated the suitability of the material, method, use of media, way of thinking and student characteristics. The purpose of this study was to obtain a comprehensive description of the implementation of didactical design of fraction division arithmetic operation in class V in terms of learning obstacles, hypothetical learning trajectory and Didactical and Pedagogical Anticipation developed by teachers based on Didactical Situation Theory and student characteristics. The research method used Didactical Design Research. The research subjects were grade V students at a public primary school located in Gugus 23 Bandung City, totalling 10 students. Data collection techniques used documentation study, lesson observation, test data collection, interview, and triangulation. The results showed that the learning obstacle that emerged after the initial didactical design was implemented in learning included psychological ontogenic obstacles, instrumental ontogenic obstacles, and ontogenic conceptual obstacle. Epistimological obstacle is the limited experience of students in solving story problems. Didactical obstacle is that students always get the solution without searching and finding it themselves. The learning trajectory found included one student who had previous learning experience related to fraction division material. Students are more interested in solving in the form of pictures and number lines, with the aim of relieving boredom in mathematics lessons. Didactical anticipation was spontaneously given, namely by providing scaffolding in understanding the meaning of the problem, for example determining the characteristics of story problems that work by means of division calculation operations, determining and changing the size of units of length, weight, and volume. Based on the research results obtained, to overcome the various problems that arose during the implementation of the initial didactical design, the authors recommend an alternative solution in the form of a revised didactical design that has been modified for use with students with different characteristics.